GTDB-Tk: a toolkit to classify genomes with the Genome Taxonomy Database - Chaumeil, Pierre-Alain; Mussig, Aaron J; Hugenholtz, Philip; Parks, Donovan H (Bioinformatics, 2019)
Abstract Summary The Genome Taxonomy Database Toolkit (GTDB-Tk) provides objective taxonomic assignments for bacterial and archaeal genomes based on the GTDB. GTDB-Tk is computationally efficient and able to classify thousands of draft genomes in parallel. Here we demonstrate the accuracy of the GTDB-Tk taxonomic assignments by evaluating its performance on a phylogenetically diverse set of 10 156 bacterial and archaeal metagenome-assembled genomes. Availability and implementation GTDB-Tk is implemented in Python and licenced under the GNU General Public Licence v3.0. Source code and documentation are available at: https://github.com/ecogenomics/gtdbtk. Supplementary information Supplementary data are available at Bioinformatics online.